Hypoxia-responsive ionizable liposome delivery siRNA for glioma therapy - Liu HM (Dove Medical Press, 2017)
Hong-Mei Liu,1,2,* Ya-Fei Zhang,1,2,* Yan-Dong Xie,1,2 Yi-Fan Cai,1,2 Bai-Yang Li,1,2 Wen Li,3 Ling-Yu Zeng,4 Yu-Ling Li,4 Ru-Tong Yu1,2 1Department of Neurosurgery, Brain Hospital, Affiliated Hospital of Xuzhou Medical University, 2Department of Neurosurgery, Institute of Nervous System Diseases, Xuzhou Medical University, 3Department of Hematology, Affiliated Hospital of Xuzhou Medical University, 4Department of Chemistry, School of Chemistry and Chemical Engineering, Jiangsu Normal University, Xuzhou, Jiangsu, People’s Republic of China *These authors contributed equally to this work Abstract: Here, we report the hypoxia-responsive ionizable liposomes to deliver small interference RNA (siRNA) anticancer drugs, which can selectively enhance cellular uptake of the siRNA under hypoxic and low-pH conditions to cure glioma. For this purpose, malate dehydrogenase lipid molecules were synthesized, which contain nitroimidazole groups that impart hypoxia sensitivity and specificity as hydrophobic tails, and tertiary amines as hydrophilic head groups. These malate dehydrogenase molecules, together with DSPE-PEG2000 and cholesterol, were self-assembled into O'1,O1-(3-(dimethylamino)propane-1,2-diyl) 16-bis(2-(2-methyl-5-nitro-1H-imidazol-1-yl)ethyl) di(hexadecanedioate) liposomes (MLP) to encapsulate siRNA through electrostatic interaction. Our study showed that the MLP could deliver polo-like kinase 1 siRNA (siPLK1) into glioma cells and effectively enhance the cellular uptake of MLP/siPLK1 because of increased positive charges induced by hypoxia and low pH. Moreover, MLP/siPLK1 was shown to be very effective in inhibiting the growth of glioma cells both in vitro and in vivo. Therefore, the MLP is a promising siRNA delivery system for tumor therapy. Keywords: hypoxia responsive, cellular uptake, siRNA delivery, ionizable liposome, hypoxic conditions